2013
DOI: 10.4172/2161-0436.1000107
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Caudal Regression Syndrome

Abstract: Caudal regression syndrome (CRS) is a rare congenital disorder in which lumbosacral anomalies are combined with anorectal and urogenital malformations. However, the molecular mechanisms of human CRS are not yet known. Trauma, nutritional problems, toxic agents, and genetics are suggested in the etiology of CRS. To the best of our knowledge, linkage studies of families affected exclusively by CRS or total sacral agenesis have not been conducted. In spite of the small number of familial cases reported, some spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 115 publications
1
28
0
7
Order By: Relevance
“…Maternal type 1 diabetes confers a higher relative risk (252) for CRS than for any congenital diosorder [9]. The exact mechanism by which maternal diabetes affects fetal development in humans remains unclear [10]. While animal studies have shown that embryos exposed to higher levels of glucose develop growth anomalies, hyperglycemia has not been associated with abnormal fetal development in humans [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal type 1 diabetes confers a higher relative risk (252) for CRS than for any congenital diosorder [9]. The exact mechanism by which maternal diabetes affects fetal development in humans remains unclear [10]. While animal studies have shown that embryos exposed to higher levels of glucose develop growth anomalies, hyperglycemia has not been associated with abnormal fetal development in humans [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several mutated genes including Cyp26a1 , Hoxd13 [25], Wnt-3a [26], Acd , Ptf1a , and Pcsk5 underlie a CRS-like phenotype in mice [10, 27], yet mutations in the human orthologs have never been identified in CRS patients. Interestingly, the reverse is also true; Mnx1 (formerly Hxlb9 ) mutant mice do not present Currarino syndrome features [28].…”
Section: Introductionmentioning
confidence: 99%
“…This disturbance may result in lesions varying from minor changes in vertebrae to complete fusion of the lower limbs. 3 The embryological defect occurs at the mid-posterior axis of the mesoderm leading to arrest of progression of the mesoblastic caudal bud. Studies of axial mesoderm patterning at early gestation suggest that one or more processes of primitive streak migration, neutralisation or differentiation are compromised.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…The prevalence of CRS is estimated to be one in 25,000 live births (3). Genetic mutations in the coding sequences of HOXD13, CYP26A1, and HLXB9 have been suspected in the pathogenesis of CRS (4). Other factors likely to contribute include chromosomal abnormalities, vascular hypoperfusion, hyperglycemia, and exposure to minoxidil and trimethoprim-sulfamethoxazole (2).…”
Section: Introductionmentioning
confidence: 99%